Mapping the global mRNA transcriptome during development of the murine first molar - Landin, Maria A.; Nygård, Ståle; Shabestari, Maziar G.; Babaie, Eshrat; Reseland, Janne E.; Osmundsen, Harald (Frontiers in Genetics, 2015)
The main objective of this study was to map global gene expression in order to provide information about the populations of mRNA species participating in murine tooth development at 24 h intervals, starting at the eleventh embryonic day (E11.5) up to the seventh post-natal day (P7). The levels of RNA species expressed during murine tooth development were mesured using a total of 58 deoxyoligonucleotide microarrays. Microarray data was validated using real-time RT-PCR. Differentially expressed genes (p<0.05) were subjected to bioinformatic analysis to identify cellular activities significantly associated with these genes. Using ANOVA the microarray data yielded 4362 genes as being differentially expressed from the elleventh embryonic day (E11.5) up to seven days post-natal (P7), 1921 of these being genes without known functions. The remaining 2441 genes were subjected to further statistical analysis using a supervised procedure. Bioinformatic analysis results for each time-point studied suggests that the main molecular functions associated with genes expressed at the early pre-natal stages (E12.5-E18.5) studied were cell cycle progression, cell morphology, lipid metabolism, cellular growth, proliferation, senescence and apoptosis, whereas most genes expressed at post-natal and secretory stages (P0- P7) were significantly associated with regulation of cell migration, biosynthesis, differentiation, oxidative stress, polarization and cell death. Differentially expressed genes (DE) not described earlier during murine tooth development; Inositol 1, 4, 5-triphosphate receptor 3 (Itpr3), metallothionein 1(Mt1), cyclin-dependent kinase 4 (Cdk4), cathepsin D (Ctsd), keratin complex 2, basic, gene 6a (Krt2-6a), cofilin 1, non-muscle (Cfl1), cyclin 2 (Ccnd2), were verified by real-time RT-PCR.